2017
DOI: 10.18632/oncotarget.22557
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of platelet to lymphocyte ratio in esophageal cancer: A meta-analysis

Abstract: PurposeThe prognostic role of inflammation index like platelet to lymphocyte ratio (PLR) in esophageal cancer remains controversial. We evaluated the prognostic significance of PLR in esophageal cancer patients.MethodsWe searched databases to identify relevant literatures. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated. A meta-analysis was performed to evaluate the prognostic value of PLR in patients with esophageal cancer.ResultsA total of 6,699 patients from 16 studies (17 coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
(41 reference statements)
0
23
0
1
Order By: Relevance
“…On the other hand, lymphocytes produce cytotoxic factors that enhance antitumor immune responses. 70 Increased platelet/ lymphocyte ratio (PLR) is associated with a higher recurrence rate and poorer prognosis of patients with HCC after hepatectomy. 69 Our results supported that neutrophil/lymphocyte ratio (NLR) could be used as an independent prognostic factor for HCC after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, lymphocytes produce cytotoxic factors that enhance antitumor immune responses. 70 Increased platelet/ lymphocyte ratio (PLR) is associated with a higher recurrence rate and poorer prognosis of patients with HCC after hepatectomy. 69 Our results supported that neutrophil/lymphocyte ratio (NLR) could be used as an independent prognostic factor for HCC after hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies with 2,513 patients were included in their study. In a study by Zhao et al, 43 16 studies including 6,699 patients were utilized to investigate the prognostic role of PLR in EC patients. All these meta-analyses found that high NLR and PLR were associated with poor survival in EC.…”
Section: Discussionmentioning
confidence: 99%
“…The predicted role of PLR has been studied among various cancers. For example, Zhao et al [ 36 ] evaluated the prognostic significance of PLR in esophageal cancer patients with a total of 6699 patients from 16 studies. The results demonstrated that higher PLR predicted poorer OS, DFS, and CFS.…”
Section: Discussionmentioning
confidence: 99%